Evaluation of alumina reinforced oil fly ash composites prepared by spark plasma sintering. Issue 4 (24th February 2020) - Ali, Sadaqat; Ahmed, Bilal Anjum; Irshad, Hafiz Muzammil; Bakare, Akolade Idris; Hakeem, Abbas Saeed; Qamaruddin, Muhammad; Ehsan, Muhammad Ali; Ali, Sameer; Azam, Muhammad Umar
Abstract: The thermomechanical behavior of micro/nano‐alumina (Al2 O3 ) ceramics reinforced with 1‐5 wt.% of acid‐treated oil fly ash (OFA) was investigated. Composites were sintered using spark plasma sintering (SPS) technique at a temperature of 1400°C by applying a constant uniaxial pressure of 50 MPa. It was evaluated that the fracture toughness of micro‐ and nanosized composites improved in contrast with the monolithic alumina. Highest fracture toughness value of 4.85 MPam 1/2 was measured for the nanosized composite reinforced with 5 wt.% OFA. The thermal conductivity of the composites (nano‐/microsized) decreased with the increase in temperature. However, the addition of OFA (1‐5 wt.%) in nanosized alumina enhanced the thermal conductivity at an evaluated temperature. Furthermore, a minimum thermal expansion value of 6.17 ppm*K −1 was measured for nanosized Al2 O3 /5 wt.% OFA composite. Microstructural characterization of Al2 O3 ‐OFA composites was done by x‐ray diffraction and Raman spectroscopy. Oil fly ash particles were seen to be well dispersed within the alumina matrix. Moreover, the comparative analysis of the nano‐/microsized Al2 O3 /OFA composites shows that the mechanical and thermal properties were improved in nanosized alumina composites. Abstract :